2016
DOI: 10.1002/adfm.201505524
|View full text |Cite
|
Sign up to set email alerts
|

Composite Nanostructures of TiO2 and ZnO for Water Splitting Application: Atomic Layer Deposition Growth and Density Functional Theory Investigation

Abstract: The commercialization of solar fuel devices requires the development of novel engineered photoelectrodes for water splitting applications which are based on redundant, cheap, and environmentally friendly materials. In the current study, a combination of titanium dioxide (TiO2) and zinc oxide (ZnO) onto nanotextured silicon is utilized for a composite electrode with the aim to overcome the individual shortcomings of the respective materials. The properties of conformal coverage of TiO2 and ZnO layers are design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…iii. One-dimensional ZnO nanostructures have been intensively investigated in photoelectrochemical (PEC) cells to split water and large enhancements have been achieved [74,77,79,[82][83][84]. Furthermore, ZnO nanorods have been reported in the applications of photoelectron-oxidation of ethanol and methanol [83,84]; ZnO has also been applied as an important photoelectrocatalyst component in the methanol production from CO 2 by photoelectrocatalytic reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…iii. One-dimensional ZnO nanostructures have been intensively investigated in photoelectrochemical (PEC) cells to split water and large enhancements have been achieved [74,77,79,[82][83][84]. Furthermore, ZnO nanorods have been reported in the applications of photoelectron-oxidation of ethanol and methanol [83,84]; ZnO has also been applied as an important photoelectrocatalyst component in the methanol production from CO 2 by photoelectrocatalytic reduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is broadly accepted that hybrid catalysts will enhance photocatalytic properties in comparison to individual semiconductor catalysts [77,78]. For example, Sun et al found that the photo-degradation efficiency of MB over ZnO nanorod arrays (NRs) was significantly enhanced by decoration with Au (ZnO/Au composite) [187].…”
Section: Degradation Of Methylene Blue (Mb)mentioning
confidence: 99%
See 1 more Smart Citation
“…photoexcitation of semiconductor photoanode; the separation and migration of photoinduced carriers; the surface water reduction on the cathode; and water oxidation on the photoanode with photoinduced electrons/holes. [20][21][22] For instance, via constructing semiconductor heterojunction with matched band position, the separation and transportation of photoinduced carrier can be effectively enhanced (such as Bi 2 MoO 6 /Si, [23] Ag/Fe 2 O 3 , [24] NiFe-LDH/C 3 N 4[25] heterojunction). [12,13] Metal oxides (MOs), such as TiO 2 , [14] α-Fe 2 O 3 , [15] and WO 3 , [16,17] have been widely investigated as the photoanode materials for PEC water splitting, for their low-cost, environmentfriendly properties.…”
mentioning
confidence: 99%
“…Likewise, the deposition process was naturally imported to make hierarchical nanostructure in terms of formation thin film structure on the metal oxide nanostructure. The deposition process was conducted by using various vacuum-based equipment such as atomic layer deposition (ALD), [40][41][42][43] chemical-vapor deposition, 21 E-beam evaporator, 44,45 pulsed laser deposition (PLD) 46,47 and sputtering 48 on the metal oxide nanostructures. By this way, a robust and dense thin film structure was accurately formed from only several nanometers to tens of nanometers onto the metal oxide nanostructure, obtained hierarchical nanostructure by controlling deposition processing conditions.…”
Section: Surface Engineering Routes For Metal Oxide Nanostructurementioning
confidence: 99%